PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW II DISERTAI EMBEDDED-TEST TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XI IPA SMAN 1 LENGAYANG KABUPATEN PESISIR SELATAN - Arieska, Ovi Lidia (Pendidikan Matematika, 2014)
This research is motivated by student less moment concentration while learning and understanding of mathematical concepts students are still low. This study aims to determine whether there is any effect of the application of cooperative learning model Jigsaw II with Embedded-Test the ability of the students understanding of mathematical concepts. This research is a pre-experiment with one shot case study design use simple linier regression. The population in this study were students class XI IPA SMAN 1 Lenganyang enrolled in the school year 2014/2015. The sampling technique was randomly. The sample in this study is a class XI IPA3. The instrument used in this study is the final test. Based on the analysis of the data shows that there are significant cooperative learning model Jigsaw II with the Embedded-Test for the math concepts students comprehenshion. 55,74% variations in understanding the concept influenced by Jigsaw II with Embedded-Test. That means there is some positive relationship or the direction of a relationship between cooperative learning model Jigsaw II a long with understanding the concept of Embedded-Test.